PENGGUNAAN ZAT WARNA DAUN MANGGA LALIJIWO (Mangifera indica L) DALAM SEDIAAN PEWARNA RAMBUT - Yuniarti, Rafita; Lubis, Minda Sari; Lubis, Zulkifli Ismail (UNIVERSITAS SARI MUTIARA INDONESIA, 2018)
Hair is something that grows from within the skin, grows as horns, and is spread almost all over the skin of the body, face, and head, except on the lips, palms of the hands and soles of the feet. Mango leaves (Mangifera indica L) from the Anacardiaceae family are plants that contain anthocyanins, in which mango leaves are expressed in red, purple and blue colors. The purpose of this study was to determine that mango leaf dye (Mangifera indica L) can be used in hair dye preparations with the addition of pyrogalol, copper (II) sulfate, xanthan gum, and the concentration of mango leaf dye extract which produces a more intense color. dark.